Inequity in access to bDMARD care and how it influences disease outcomes across countries worldwide: results from the METEOR-registry. Issue 10 (6th July 2018) - Bergstra, Sytske Anne; Branco, Jaime C; Vega-Morales, David; Salomon-Escoto, Karen; Govind, Nimmisha; Allaart, Cornelia F; Landewé, Robert B M
Abstract : Objective: To establish in a global setting the relationships between countries' socioeconomic status (SES), measured biological disease modifying antirheumatic drug (bDMARD)-usage and disease outcomes. To assess if prescription and reimbursement rules and generic access to medication relates to a countries' bDMARD-usage. Methods: Data on disease activity and drug use from countries that had contributed at least 100 patients were extracted from the METEOR database. Mean disease outcomes of all available patients at the final visit were calculated on a per-country basis. A questionnaire was sent to at least two rheumatologists per country inquiring about DMARD-prices, access to treatment and valid regulations for prescription and reimbursement. Results: Data from 20 379 patients living in 12 different countries showed that countries' SES was positively associated with measured disease activity (meanDAS28), but not always with physical functioning (HAQ-score). A lower country's SES, stricter rules for prescription and reimbursement of bDMARDs as well as worse affordability of bDMARDs were associated with lower bDMARD-usage. bDMARD-usage was negatively associated with disease activity (although not with physical functioning), but the association was moderate at best. Conclusions: Disease activity in patients with rheumatoid arthritis as well as bDMARD-usage varies across countries worldwide. The (negative) relationship between countries' bDMARD-usage and level of disease activity is complex and under the influence of many factors, including—but not limited to—countries' SES, affordability of bDMARDs and valid prescription and reimbursement rules for bDMARDs.